STUDY ON OPTIMIZATION OF LIME SLURRY MAKING AS PH REGULATOR FOR FLOTATION OF SULFIDE ORE AT PT AMMAN MINERAL NUSA TENGGARA - Sebastianus Sihaloho, Three
PT Amman Mineral Nusa Tenggara (PT AMNT) is a mining company in Indonesia that processes copper ore. The ore processed at PT AMNT contains some valuable minerals, namely chalcopyrite (CuFeS2) and bornite (Cu5FeS4), and impurities minerals, namely pyrite (FeS2) and silica (SiO2). PT AMNT processes copper sulfide ore with the help of a chemical medium i.e. lime as a pH regulator in flotation process. There are 2 types of lime used, namely pebble and hydrated limes. The consumption of lime used at PT AMNT is quite high and not optimal. Optimization in the use of lime as a pH regulator is needed to reduce lime consumption. A series of experiments were carried out, beginning with lime sampling from PT AMNT QA & QC laboratory and from the lime plant area (hydrocyclone, tank 15 and tank 16), as well as rougher row 5 concentrate samples. Then, the samples taken were prepared with a filter press and oven. After the sample was prepared, the sample was subjected to sieving analysis to determine the particle size distribution of the sample. In this experiment, It was also studied the effect of percent solids, percent Santong water (acid mine water coming from the Santong area), and the initial water temperature on reactivity, pH lime slurry, and lime consumption respectively. Lime reactivity analysis was carried out on lime samples with initial water temperature variations of 25 - 35oC (pebble lime; and hydrated lime of 40 - 60oC), percent solids of 10-25%, and percent water Santong of 0-100%. When measuring lime slurry pH and lime consumption, the same variations were made as in the reactivity analysis. The results of lime slurry particle size distribution obtained in tank 15 and tank 16 showed a p50 value of 0.065 mm - 0.070 mm. The results of lime reactivity analysis showed that the type of PAS lime was classified as high-reactivity lime (reactivity value> 30oC/s), and Uniserve and hydrated limes were classified as unreactive lime (reactivity value <10oC/s) respectively. The optimal consumption of lime and lime slurry making was in a condition of Santong water at 75%, solid percent at 20%, and initial water temperature at 25oC (pebble lime; and hydrated lime at 40oC). Under these optimal conditions, the value of Uniserve lime consumption was 10.76 tons/DMT, PAS lime consumption was 4.77 tons/DMT, and hydrated lime consumption was 3.97 tons/DMT. When compared with the initial lime consumption value at PT AMNT with the same conditions, the Uniserve lime consumption value is 12.39 tons/DMT, PAS lime consumption is 6.48 tons/DMT, and hydrated lime consumption is 5.14 tons/DMT.